Pengaruh Media Video Senam Hipertensi terhadap Peningkatan Keterampilan Lansia - Farlina Nur Islami; Emelia Tonapa; Desie Rahmawati; Dwi Hendriani (Yayasan Literasi Sains Indonesia, 2026)
Deaths due to hypertension totaled 427,218, highlighting the serious impact of this disease on health. At the Bengkuring Community Health Centre, there are 1,143 elderly suffering from hypertension, making hypertension the primary cause of stroke and heart failure, particularly among elderly due to degenerative processes and a sedentary lifestyle that lacks physical activities such as exercise. The ability of the elderly to practice hypertension exercises remains very limited due to a lack of regular exercise. This situation calls for innovative and practical educational strategies, such as the use of videos, to improve hypertension exercise skills among the elderly. The purpose of this study was to analyze the effect of a hypertension exercise video on improving the skills of elderly at the Bengkuring Community Health Center using a one-group pre-test and post-test pre-experimental design. A purposive sampling technique was used to select 46 elderly. After using an observation sheet to collect skill data, the Wilcoxon test was used to analyze the statistics. With a p-value of 0.000 (p<0.05), the results of the study indicate that the skills of the elderly improved after receiving the hypertension exercise video intervention. In conclusion, education through Hypertension exercise videos is effective in improving practical exercise skills among the elderly.